Synoptic reporting in Mohs micrographic surgery. (20th August 2019) - Cabrera, Samantha; Smith, Saxon; Ryman, William
Abstract: There is currently no standardised reporting format for Mohs surgery with its operation reports mostly written in a narrative form making them prone to unintentional errors and omission of necessary data. Synoptic histology reporting is used to describe excised skin cancers such as melanomas and, more recently, squamous cell and basal cell carcinomas. Since Mohs surgery is utilised as the gold standard treatment for locally invasive squamous and basal cell carcinomas, we propose the use of our model of synoptic reporting to ensure the completeness and consistency of Mohs surgery operation reports.